The Impact of Digital Marketing Management on Customers Buying Behavior: Case Study of Soran City (Entrepreneurship Journal for Finance and Business, 2024)
This study presents the impact of digital marketing on customer buying behavior and examines how digital marketing channels, such as social networks, search engines, and emails, influence customers’ purchasing behavior. The main purpose was to investigate the influence of digital marketing on customer's behavior and identify effective platforms for businesses in Soran independence administration to retain customers. The methodology of the study utilizes a quantitative approach through a survey questionnaire to gather data on the impact of digital marketing on customer buying behavior, including variables such as age, gender, income, education level, and online shopping behavior. The data is analyzed using statistical Package for social science (SPSS 26.0) to determine the relationship and effects of these variables on customer behavior. The study collected data from 250 participants who responded to a survey questionnaire distributed online to customers and people of Soran independence administration in several cities, districts, and sub-districts. The sample was appropriate, simple random sampling, and composed of demographic variables, questions about digital marketing, and purchasing behavior. The results of the study show that digital marketing has a significant impact on customer buying behavior, especially among younger and higher-educated people in Soran independence administration; it provides cost-effective and efficient ways for customers to fulfill their needs. However, businesses should be transparent to avoid deceiving customers. Digital marketing has a positive impact on customer satisfaction, but challenges such as timely delivery and over-advertising on social media remain and. Digital marketing has a significant impact on customer buying behavior, influenced by factors like education level, income, and social media usage. Valid factor analysis test supports this conclusion.Keywords: Digital marketing management, Customers buying behavior, Social media, Instagram, Facebook.